Solid Waste Composition and Management in Phu Huu Eco-Tourism Area, Hau Giang Province, Vietnam - Giao, Nguyen Thanh (International Journal of Environment, Agriculture and Biotechnology, 2020)
The study was conducted to evaluate the current status of solid waste management in PhuHuu Eco-Tourism Area in HauGiang Province, Vietnam in 2019. The main research method was to interview managers and visitors to the place. In addition, the study also aimed to classify and estimate daily generated solid waste. The results presented that the rate of generation of solid waste was 0.3 kg/person/day, with total solid wastes of 70-100 kg/day for weekdays and 200-300 kg/day for weekends and holidays. The organic components accounted for 69% including rice, leftovers, spoiled vegetables, fruit peels and leaves while inorganic components occupied 31% including plastic cups, straws, plastic wrap and foam boxes. Results of interviews with visitors indicated that the majority of tourists did not agree with the arrangement of rubbish bins and solid waste management in the tourist area. Solid waste management is not efficient due to the arrangement and the size of the waste bins, as well as the methods of solid waste classification. There is a need for better management of solid in the waste tourism area to attract more tourists to visit.